Assessment of the genetical relationship of tiger shrimps (Penaeus monodon) in Sarawak using AFLP fingerprinting - Lim Mui Hua (Jabatan Perikanan Malaysia, 2015)
A total of 18 samples (200-500 g/sample) of tiger shrimps (Penaeus monodon) were collected from January to September 2007 for determination of the A total of 18 samples (200-500 g/sample) of tiger shrimps (Penaeus monodon) were collected from January to September 2007 for determination of the genetical relationship of tiger shrimps (Penaeus monodon) in Sarawak. Among these, 15 samples were obtained from the tiger shrimp farms in Kuching Region (Sempadi, Santubong, Salak) and Sarikei Region (Selumit, Belawai). The other three samples were collected from the marine capture tiger shrimps in the waters off Baram, Miri Region. A triplicate samples were used for every sample to undergo DNA fingerprinting using Amplified Restriction Fragment Polymorphism (AFLP) technique. Results showed that there were a similarity in genetic composition between the tiger shrimps of Kuching Region and Sarikei Region but different to the tiger shrimps in Miri Region. This paper represents a first preliminary and baseline study to assess the genetical relationship of tiger shrimps in the aquaculture farms and marine waters in Sarawak. There is a need to establish the genetic profiling database of tiger shrimps in Sarawak for future selection of quality tiger shrimp population to be used in the aquaculture industry.